2017
DOI: 10.1051/matecconf/201711800028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tractor particulate emissions in a modified NRSC test after implementing a particulate filter in the exhaust system

Abstract: Abstract. Retrofitting, which means retrofitting old generation engine systems with modern exhaust aftertreatment systems, is becoming increasingly popular, which allow vehicles to adhere to the newer and more stringent emission norms. This can save the operators of such vehicles money using older engineered designs without the need to design a new unit or buy an expensive new machine or vehicle. At present, there is a growing interest in emissions from off-road vehicles and the introduction of minimum limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Abd-Alrazzaq et al [17] selected a conventional center lathe machine as a good candidate for the CNC retrofit; this is a low-cost solution that can ensure the high quality of the parts. Siedlecki et al [18] analyzed retrofitting of a farm tractor with a universal particle filter with the size chosen relative to engine displacement, finding that this alternative saves money and reduces emissions. Quatrano et al [19] retrofitted a CNC machine, considered obsolete due to high maintenance costs, by using low-cost off-the-shelf components and through open-source software to reduce the amount of electronic and industrial wastes.…”
Section: Criteria For Assessing the Sustainability Of Production Syst...mentioning
confidence: 99%
“…Abd-Alrazzaq et al [17] selected a conventional center lathe machine as a good candidate for the CNC retrofit; this is a low-cost solution that can ensure the high quality of the parts. Siedlecki et al [18] analyzed retrofitting of a farm tractor with a universal particle filter with the size chosen relative to engine displacement, finding that this alternative saves money and reduces emissions. Quatrano et al [19] retrofitted a CNC machine, considered obsolete due to high maintenance costs, by using low-cost off-the-shelf components and through open-source software to reduce the amount of electronic and industrial wastes.…”
Section: Criteria For Assessing the Sustainability Of Production Syst...mentioning
confidence: 99%
“…For the power and emission measurements, the same R100 according to DIN 51605 was used as in field operations. The diesel fuel at the tractor test stand complied with CEC legislative fuel RF 06-03 based on test procedure ISO 8178-1 [18,[24][25][26][27].…”
Section: Fuelsmentioning
confidence: 99%
“…For the emission measurements of tractors on a test bench, no standard is available. In several research projects, a procedure based on ISO 8178-1 was used [18,[24][25][26][27] and showed good reproducibility in a small-scaled round robin test [26]. Here, the tractors were operated using the C1 test cycle according to ISO 8178-4.…”
Section: Power and Emission Measurementmentioning
confidence: 99%
“…Reducing fuel consumption also has its economic justification, because it reduces transport costs [1,2]. Therefore, in relation to combustion engines produced even ten years ago, emission factors and fuel consumption have decreased by at least a dozen percent, which contributes to greater environmental protection and is in line with the adopted policy of sustainable development [3,4]. Railway vehicle internal combustion engines, in the aspect of pollutant emissions, are type approved only at a stationary dynamometer stations.…”
Section: Introductionmentioning
confidence: 99%